Spatiotemporal analysis of Plasmodium falciparum erythrocyte binding antigen-175 gene dimorphism in Ghana - Abraham Y. Kpirikai; Belinda A. Ofosu; Josie N. A. Okai; Victor Kornu; Abdul Rashid Kassim; Esther Donkor; Frederica Malm; Osumanu Ahmed; Mona-Liza E. Sakyi; Samirah Saiid; Albert Yao Kudakpo; Charles Mensah; et al. (Malaria Journal)
Abstract Background Malaria remains a leading cause of death worldwide, claiming over 600,000 lives each year. Over 90% of these deaths, mostly among children under 5 years, occur in sub-Saharan Africa and are caused by Plasmodium falciparum. The merozoites stage of the parasite, crucial for asexual development invade erythrocytes through ligand-receptor interactions. Erythrocyte binding antigen (EBA)-175 is one of the key ligands facilitating invasion via interaction with glycoprotein A (GpA) receptors on the erythrocytes. EBA-175 is known to exist in two dimorphic allelic (F and C) forms with each found to infer different virulence. There is paucity of data on the prevalence of these alleles and their epidemiology in the Ghanaian malaria landscape and hence this study. Methods Parasite gDNA was extracted from archived Dried Blood Spots (DBS) prepared from 700 confirmed malaria-infected individuals and analysed for P. falciparum EBA-175 dimorphism. Selective eba-175 gene amplification via nested PCR and allele scoring using agarose gel electrophoresis for F, C and F/C alleles. Results Of the total 632 successfully genotyped samples, prevalence of F, C, and F/C allelic forms were 61.2% (n = 387), 20.7% (n = 131), and 18.0% (n = 114), respectively. Seasonality analysis did not reveal a statistically significant difference in the prevalence of dimorphic forms between the wet (n = 475) and dry (n = 157) seasons (p = 0.051). The prevalence ratio (wet/dry) for C, F and F/C were determined to be 1.0, 1.1 and 1.4, respectively. Between 2019 and 2022, the prevalence of the alleles changed significantly (χ2 = 6.5427, p = 0.03). Geometric mean parasite density for the C, F, and F/C alleles were 21,477.1 [95%CI 15,749.2 − 29,288.1], 18,308.0 [95%CI 15,149.9–22,124.5] and 22,690.4[95% CI 16,891.9–30,479.2], respectively. Conclusion The F-allele was the most prevalent form across all age groups, followed by the C allele and mixed F/C alleles. No significant difference in allele prevalence was observed between the high malaria season (wet) and low malaria season (dry). However, a statistically significant difference in the temporal prevalence of pure alleles (F & C) between two time points was observed. The current study adds to the existing body of knowledge on eba-175 allelic dimorphism and highlights the co-circulation of alleles in high malaria endemic areas in Ghana.